Prevalence of Bovine Viral Diarrhea Virus in Ovine and Caprine Flocks: A Global Systematic Review and Meta-Analysis - Diao, Nai-Chao; Chen, Zi-Yang; Shi, Jun-Feng; Wang, Qi; Sheng, Chen-Yan; Ma, Bao-Yi; Yang, Yang; Sun, Yu-Han; Shi, Kun; Du, Rui (Frontiers in Veterinary Science, 2021)
Background: Bovine viral diarrhea virus (BVDV) is the causative agent of bovine viral diarrhea. It can infect cattle, sheep, pigs, and other animals, causing diarrhea, miscarriage, and stillbirth, among other symptoms, and it can result in huge economic losses to animal husbandry. There are reports on BVDV infection rates in sheep and goat herds from all over the world and this meta-analysis aimed to evaluate the prevalence of and risk factors for BVDV in sheep and goats. Results: Using the data of 41,297 sheep and goats in 24 countries/regions to calculate a comprehensive prevalence rate for BVDV. The overall prevalence of BVDV infection in sheep and goats was estimated to be 8.6% (95% CI: 5.2-12.7) by immunological methods and 7.3% (95% CI: 2.7-13.7) by molecular methods. Analysis by national income level revealed that prevalence is higher in middle-income countries than in high-income countries (P < 0.05). The study also compared prevalence rates by species of BVDV, sampling year, and test species, but did not find significant differences. Conclusion: This systematic review and meta-analysis is the first to determine the global prevalence of BVDV in ovine and caprine flocks. The prevalence of BVDV in sheep and goat populations varies from region to region, and the situation is not optimistic in some countries.